Illustrator CS2 killer tips - Cross, Dave (New Riders, 2005)
Over 300 productivity-enhancing secrets you need to know about Illustrator CS. Fully illustrated, stand-alone tips reveal the hidden features and productivity-enhancing tricks that allow you to accomplish more in less time with Illustrator CS2. Easy-to-browse format lets you find and apply information instantly and includes many tips and techniques that focus on Illustrator CS2's new features: Converting bitmaps into vectors with Live Trace, Painting with the new Live Paint tool, creating Custom Workspaces, and more.